Prevalence of the SdhC I86F substitution associated with resistance to SDHI fungicides in populations of the Asian soybean rust pathogen in Brazil in recent cropping seasons - Krug, Loane Dantas [UNESP]; Ceresini, Paulo Cezar [UNESP]; Moreira, Silvino Intra [UNESP]; Pereira, Davi Jacinto [UNESP]; de Deus Paes Gonçalves, Lucas Matheus [UNESP]; Acerbi, Amanda Regina [UNESP]; de Lima Montan, Rafael Ristori [UNESP]; Leardine, Gabriela Valério [UNESP]; de Moura, Suzany Santos [UNESP]; Portalanza, Diego; Garcés-Fiallos, Felipe Rafael (Springer Nature, 2025)
Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi (Pp), is the most important disease of soybean crops in Brazil. For over a decade, disease management has strategically focused on extensive, prophylactic applications of systemic, single-site chemical fungicides with high risk for resistance (especially QoIs and DMIs). Due to widespread resistance to QoIs and DMIs in the country, the efficacy of these site-specific fungicides has significantly decreased, resulting in yield losses below 20%. Since 2013, new succinate dehydrogenase inhibitor (SDHI) fungicides, also site-specific, have been included in the chemical management portfolio for ASR. However, during the 2015/2016 season, Pp isolates with a mutation in the SdhC gene were detected, resulting in the substitution of the amino acid SdhC-I86F at the target site, conferring resistance to SDHI fungicides. Subsequent surveys until 2019 indicate that SDHI resistance has become pervasive in the country. Our study aimed to determine, using specific real-time quantitative PCR (RT qPCR) detection of the SdhC-I86F mutation, the prevalence of this substitution in field populations of the ASR pathogen sampled during the 2020/21 and 2022/23 seasons in different Brazilian states. We obtained 51 Pp samples from Bahia, Goiás, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Paraná, Rio Grande do Sul, and São Paulo. We also determined the EC50 (fungicide concentration sufficient to reduce in vivo ASR severity by 50%) in samples from six distinct pathogen populations where the SdhC-I86F substitution was detected. The SdhC 86F mutant allele associated with SDHI resistance was detected in the majority Pp populations sampled. The six phenotyped populations showed reduced sensitivity to the fungicide fluxapyroxad. We conclude that the SdhC-I86F substitution remained prevalent in the country in recent cropping seasons.
Keywords: Fluxapyroxad; Phakopsora pachyrhizi; SdhC-I86F substitution; Succinate dehydrogenase inhibitors